Nomenclatural changes in Neotropical Tracheini with the description of Hylaeogena aeneonitens sp. nov. (Coleoptera: Buprestidae) from the Orinoco basin in Venezuela - Hornburg, Michael (Zootaxa, 2012)
Investigations of specimens belonging to the genus Hylaeogena Obenberger, 1923 from South America and especiallyfrom Venezuela and corresponding types in European institutional collections has led to the detection of a number of newsynonyms and new combinations. These proposed nomenclatural changes are for species in the genera Hylaeogena Oben-berger, 1923 and Pachyschelus Solier, 1833. The following nomenclatural changes are proposed: Hylaeogena atroviridis(Fisher, 1922) = H. insidiosa Cobos, 1978 syn. nov. = H. venezuela Bellamy, 1996 syn. nov., Hylaeogena capitata (Ker-remans, 1903) comb. nov., Hylaeogena cincta (Waterhouse, 1889) = H. circumciliata Cobos, 1967 syn. nov., Hylaeogenacircularis (Kerremans, 1899) = H. bruchi (Kerremans, 1903) syn. nov. = H. scutellaris Obenberger, 1925 syn. nov., Hy-laeogena circumdata (Kerremans, 1897) comb. nov. = H. achardi Obenberger, 1925 syn. nov., Hylaeogena circumscripta(Kerremans, 1903) = H. bryanti Théry, 1940 syn. nov., Hylaeogena speculum (Klug, 1827) = H. cordieri Obenberger,1923 syn. nov., and Pachyschelus lunifer Waterhouse, 1889 comb. nov. Lectotype and paralectotype for H. speculum(Klug) are designated. Hylaeogena aeneonitens sp. nov. from the Orinoco basin in Venezuela is described and illustrated. Furthermore, new country records for the occurrence of the genus Hylaeogena in Venezuela are given.Las investigaciones de especímenes pertenecientes al género Hylaeogena Obenberger, 1923 de Suramérica y especial-mente de Venezuela y los tipos correspondientes de colecciones institutionales europea llevó a la detección de una seriede sinónimos y combinaciones nuevas. Estos cambios nomenclaturales propuestos están afectando los géneros Hylaeoge-na Obenberger, 1923 y Pachyschelus Solier, 1833. Los cambios nomenclaturales que se sugieren son: Hylaeogena atro-viridis (Fisher, 1922) = H. insidiosa Cobos, 1978 syn. nov. = H. venezuela Bellamy, 1996 syn. nov., Hylaeogena capitata(Kerremans, 1903) comb. nov., Hylaeogena cincta (Waterhouse, 1889) = H. circumciliata Cobos, 1967 syn. nov., Hylaeo-gena circularis (Kerremans, 1899) = H. bruchi (Kerremans, 1903) syn. nov. = H. scutellaris Obenberger, 1925 syn. nov.,Hylaeogena circumdata (Kerremans, 1897) comb. nov. = H. achardi Obenberger, 1925 syn. nov., Hylaeogena circum-scripta (Kerremans, 1903) = H. bryanti Théry, 1940 syn. nov., Hylaeogena speculum (Klug, 1827) = H. cordieri Oben-berger, 1923 syn. nov. y Pachyschelus lunifer Waterhouse, 1889 comb. nov. Lectotipo y paralectotipo para H. speculum(Klug) se designan. Se describe e ilustra Hylaeogena aeneonitens sp. nov. de la cuenca del Orinoco en Venezuela. Además se publican nuevos registros de la ocurrencia del género Hylaeogena para el territorio de Venezuela.